2020
DOI: 10.1093/jaoacint/qsaa016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Culture Methods for the Detection of Bacillus cereus Group in Cosmetics

Abstract: Abstract Background The U.S. Food and Drug Administration (FDA) Bacteriological Analytical Manual (BAM) reference culture method uses Modified Letheen Broth (MLB) for microbiological analyses for all types of cosmetic products. Objective This study evaluated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Staphylococcus epidermidis was isolated in powders, blushers 11 , and various eye cosmetics 11 , 34 , 35 . Bacillus cereus isolates were previously detected in various eye cosmetics 24 , lip glosses 16 and creams 15 . Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus epidermidis was isolated in powders, blushers 11 , and various eye cosmetics 11 , 34 , 35 . Bacillus cereus isolates were previously detected in various eye cosmetics 24 , lip glosses 16 and creams 15 . Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…have been identified 2 , 10 , 11 . In creams, Escherichia coli, Bacillus spp, Bacillus cereus, Klebsiella spp., Klebsiella pneumoniae, Pseudomonas spp., Staphylococcus spp., Enterobacter spp., Enterococcus faecalis, Micrococcus spp., Staphylococcus aureus, Streptococcus pyogenes, and Enterobacter aerogenes have been detected 2 , 8 , 10 , 12 15 . Another study has shown that Escherichia hermannii, S. aureus, Bacillus cereus, and Enterobacter species were isolated from lip glosses and lipsticks.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus epidermidis was isolated in powders, blushers 9 , and various eye cosmetics 9,29,30 . Bacillus cereus isolates were previously detected in various eye cosmetics 23 , lip glosses 14 and creams 13 . Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…have been identi ed 2,8,9 . In creams, Escherichia coli, Bacillus spp, Bacillus cereus, Klebsiella spp., Klebsiella pneumoniae, Pseudomonas spp., Staphylococcus spp., Enterobacter spp., Enterococcus faecalis, Micrococcus spp., Staphylococcus aureus, Streptococcus pyogenes, and Enterobacter aerogenes have been detected 2,6,8,[10][11][12][13] . Another study has shown that Escherichia hermannii, S. aureus, Bacillus cereus, and Enterobacter species were isolated from lip glosses and lipsticks.…”
Section: Introductionmentioning
confidence: 99%